Economic fluctuations in a small economy with two productive sectors under a floating exchange rate regime (2013)
This paper presents a theoretical model of aggregate supply and demand in a small economy with two productive sectors, under a flexible exchange regime and imperfect capital mobility -- Only one of the production sectors is assumed to produce an exportable commodity sold at world market prices, while the production of the other sector is assumed to supply the domestic market -- This model helps to explain how the impact of both domestic (economic policy, productivity, etc.) and foreign (changes in exchange terms) shocks is spread -- In every case studied, results show that real output increases consistently with those cases postulated by economic theory -- Conversely, the effects on the price level, the exchange rate and the real interest rate are ambiguous -- In terms of domestic shocks, fiscal or monetary policy may be seen as a way to stabilize or stimulate the economy but the costs involved raise the price level